APLIKASI PENGELOLAAN DATA PENDUDUK DI KANTOR RW BERBASIS WEB - Tedi Supriadi; Roni Ilham Subagja; Marjito Marjito (Jurnal Computech & Bisnis (e-Journal), 2022)
AbstractThe RW17 Citaliktik Soreang office is one of the Residents' Associations having its address at Kp. Citaliktik Soreang Islamic Boarding School with various kinds of resident activities. Currently the population data collection at the Citaliktik RW17 Office is to collect citizen data in a conventional manner according to its category. With this, it is necessary to implement an information system, namely the Population Data Collection Application which is implemented through the website. By utilizing a computer or laptop device, the system will be developed using object-oriented software development and programming (OOAD) methods. With the aim of being able to assist the RW17 Citaliktik Soreang Office in improving the existing system with the hope that the processing and presentation of population data which is still conventional can make it easier to make this population data collection application. The result of making the application is a Population Data Collection Application at the RW17 Citaliktik Soreang Office.Keyword: OOAD, Data Collection, Website